An appropriate DNA input for bisulfite conversion reveals LINE-1 and Alu hypermethylation in tissues and circulating cell-free DNA from cancers. - Trang Thi Quynh Tran; Tung The Pham; Than Thi Nguyen; Trang Hien Do; Phuong Thi Thu Luu; Uyen Quynh Nguyen; Linh Dieu Vuong; Quang Ngoc Nguyen; Son Van Ho; Hang Viet Dao; Tong Van Hoang; Lan Thi Thuong Vo (PLoS ONE)
The autonomous and active Long-Interspersed Element-1 (LINE-1, L1) and the non-autonomous Alu retrotransposon elements, contributing to 30% of the human genome, are the most abundant repeated sequences. With more than 90% of their sequences being methylated in normal cells, these elements undeniably contribute to the global DNA methylation level and constitute a major part of circulating-cell-free DNA (cfDNA). So far, the hypomethylation status of LINE-1 and Alu in cellular and extracellular DNA has long been considered a prevailing hallmark of ageing-related diseases and cancer. This study demonstrated that errors in LINE-1 and Alu methylation level measurements were caused by an excessive input quantity of genomic DNA used for bisulfite conversion. Using the minuscule DNA amount of 0.5 ng, much less than what has been used and recommended so far (500 ng-2 μg) or 1 μL of cfDNA extracted from 1 mL of blood, we revealed hypermethylation of LINE-1 and Alu in 407 tumour samples of primary breast, colon and lung cancers when compared with the corresponding pair-matched adjacent normal tissue samples (P < 0.05-0.001), and in cfDNA from 296 samples of lung cancers as compared with 477 samples from healthy controls (P < 0.0001). More importantly, LINE-1 hypermethylation in cfDNA is associated with healthy ageing. Our results have not only contributed to the standardized bisulfite-based protocols for DNA methylation assays, particularly in applications on repeated sequences but also provided another perspective for other repetitive sequences whose epigenetic properties may have crucial impacts on genome architecture and human health.